Prospective Evaluation of Health-Related Quality of Life in Patients Undergoing Anterolateral Craniofacial Resection with Orbital Exenteration - Mukoyama, Nobuaki; Nishio, Naoki; Kimura, Hiroyuki; Kishi, Shinichi; Tokura, Tatsuya; Kimura, Hiroki; Hiramatsu, Mariko; Maruo, Takashi; Tsuzuki, Hidenori; Fujii, Masazumi; Iwami, Kenichiro; Takanari, Keisuke; Kamei, Yuzuru; Ozaki, Norio; Sone, Michihiko; Fujimoto, Yasushi (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study was aimed to evaluate health-related quality of life in patients undergoing anterolateral craniofacial resection (AL-CFR) with orbital exenteration (OE) for malignant skull base tumors and to investigate the effects of early psychiatric intervention.Design Present study is a prospective, observational study.Setting The study took place at the hospital department.Participants Twenty-six consecutive patients were selected who underwent AL-CFR with OE at our hospital between 2005 and 2015.Main Outcome Measures Health-related quality of life was assessed preoperatively and 3, 6, 12, and 24 months after surgery using the Hospital Anxiety and Depression Scale (HADS) and medical outcomes study 8-items Short Form health survey (SF-8). In all cases, psychiatric intervention was organized by the consultation liaison psychiatry team preoperatively and postoperatively.Results Ten (38.0%) of the 26 patients died and 16 (62.0%) were alive and disease-free at the end of the study. The 3-year overall and disease-free survival rates were 64.9% and 53.3%, respectively. Twenty-one patients (80.8%) developed psychiatric complications after surgery and needed treatment with psychotropic medication. Before surgery, 28% of patients had HADS scores ≥8 for anxiety and 20% had scores ≥8 for depression. Seven of the eight items in the SF-8 were significantly lower than those for the general Japanese population. However, scores for all the SF-8 items gradually improved during postoperative follow-up, reaching approximately 50 points, which is the national standard value, at 2 years after surgery.Conclusions Craniofacial resection with OE was feasible and well tolerated in patients with malignant skull base tumors who received early psychiatric intervention to decrease the considerable psychological impact of this procedure.
Keywords: anterolateral craniofacial resection; orbital exenteration; quality of life; skull base malignant tumor; early psychiatric intervention; hospital anxiety and depression scale; medical outcomes study 8-items short form health survey